Efficacy of sorafenib in BRAF-mutated non-small-cell lung cancer (NSCLC) and no response in synchronous BRAF wild type-hepatocellular carcinoma: a case report. Issue 1 (December 2016) - Casadei Gardini, Andrea; Chiadini, Elisa; Faloppi, Luca; Marisi, Giorgia; Delmonte, Angelo; Scartozzi, Mario; Loretelli, Cristian; Lucchesi, Alessandro; Oboldi, Devil; Dubini, Alessandra; Frassineti, Giovanni Luca; Ulivi, Paola
Abstract Background Sorafenib is a multi-targeted kinase inhibitor with a demonstrated activity in renal cell carcinoma (RCC) and hepatocellular carcinoma (HCC), and it is currently used for the treatment of these pathologies. Ongoing clinical trials are studying its activity in other malignancies, such as non-small-cell lung cancer (NSCLC). However, no biological marker is known to define either the sensitivity or resistance to the drug. Case presentation Here we report a case of a patient with two synchronous tumors, HCC and NSCLC, with metastases in the contralateral lung and bone. The patient was treated with gemcitabine as first line, with a resulting progressive disease after two months, and then with sorafenib at standard dosage in the second line setting. After 6 months of treatment CT scan showed a partial response in the primary lesion of the lung, complete response of the metastasis in the contralateral lung, and stability of HCC. The patient had progression in the lung, liver and bone after 13 months of therapy. A molecular characterization of NSCLC and HCC lesions was performed, revealing aBRAF exon 11 mutation (G469V) only in NSCLC. We hypothesize that the response observed in NSCLC lesions could be due to the presence ofBRAF mutation, and that this alteration could be responsible in determining sorafenib sensitivity. Conclusions Results observed in this case encourage further research on the activity of sorafenib in both HCC and NSCLC, based on the presence ofBRAF mutation. This could lead to a selection of HCC patients to be treated with this drug, and could help identify a novel treatment strategy forBRAF -mutated NSCLC patients.